Regional Promotion and Halal Tourism E-Marketing of Tourism Visiting Motives in Yogyakarta - Raja Ela Safira; Dhidhin Noer Ady Rahmanto; Annas Syams Rizal Fahmi (Universitas Darusssalam Gontor, 2018)
This research was conducted to find out how the influence of Halal Tourism Promotion Based on E-Marketing Against Tourist Visits in Yogyakarta. Promotion is an important thing that needs to be done and considered in attracting tourists. In this millennial era technology is developing very rapidly, so many activities are carried out using technology. Thus the use of E-Marketing is considered suitable for increasing tourists. The testing method is to use multiple linear regression method with moderating variables to show the results of the study of the influence of Halal Tourism Promotion Based on E-Marketing Against Tourist Visits in Yogyakarta. Data collection techniques used were questionnaires and observations. From the results of this study it was found that the use of E-Markenting can increase wisatawan's interest in visiting halal tourism in Yogyakarta. At first when using regional promotions only gained 7% and when using E-Marketing increased to 67%.